When those new branches grow, i will also be healed (2014)
Ruysen Flores narrates about how he overcame a spiritual illness he suffered, following the example of the plants that his teacher Pablo Amaring had taught him. As the plants renew themselves when they are pruned, so his spirit healed. His inspiration is the mythology, the traditions and the plants. In his painting there inhabits a feminine spirit, whose children are the dolphins. Ruysen paints the spirits of protection that appear in the shamanic rituals and the spirits of the plants and of the elements. He uses figures that appear in perspective, also very used by Pablo Amaringo, which he calls “tingunas”.